Polyethylene glycol-based deep eutectic solvents as a novel agent for natural gas sweetening. - Jiyad N Aldawsari; Idowu A Adeyemi; Abdelbasset Bessadok-Jemai; Emad Ali; Inas M AlNashef; Mohamed K Hadj-Kali (PLoS ONE)
Deep eutectic solvents (DESs) have received significant attention as potential extracting agents in recent years due to their favorable characteristics including low cost, easy preparation and environmentally safe starting materials. Experimentally screening for highly efficient DESs meeting various requirements for natural gas sweetening remains a challenging task. Thus, an extensive database of estimated Henry's law constants (Hi) and solubilities (xi) of CO2 in 170 different DESs at 25°C has been constructed using the COSMO-RS method to select potential DESs. Based on the COSMO-RS study, three DESs, namely tetrabutylammonium bromide (TBAB)+polyethylene glycol (PEG-8) (on a molar basis 1:4), TBAB+octanoic acid (OCT) (1:4), and methyltriphenylphosphonium bromide (MTPB)+PEG-8 (1:10), were chosen for further experimentation up to 2 bar at 25°C using a vapor-liquid equilibria (VLE) apparatus. Reliable thermophysical properties were determined experimentally, and a detailed equilibrium-based model was developed for one of the glycol-based DESs (i.e., TBAB+PEG-8 (1:4)). This information is an essential prerequisite for carrying out process simulations of natural gas sweetening plants using ASPEN PLUS. The simulation results for the proposed DES were compared to those of monoethylene glycol (MEG). Here, we find that the aqueous TBAB+PEG-8 (1:4) solvent shows ~60% lower total energy consumption and higher CO2 removal when compared to those using the MEG solvent.